MDMA and tramadol or tapentadol co-administration causes serotonin-independent neurological damage - Faria, Juliana (2025)
The simultaneous consumption and misuse of different drugs, including 3,4-methylenedioxymethamphetamine (MDMA, “ecstasy”) and opioids, raise concerns about fatal intoxications, as a result of increased serotonin levels. However, research on the simultaneous consumption of MDMA and opioids is limited. This study aimed to evaluate the toxic effect of the simultaneous exposure of the undifferentiated human SH-SY5Y neuroblastoma cell line to MDMA and tramadol or MDMA and tapentadol, focusing on serotonin toxicity. After a 48-hour exposure to the mixtures, there was a significant decrease in cell viability linked to an increase in oxidative stress, alterations in mitochondrial membrane potential, and an increase in caspase-3 activity. Additionally, increased intracellular glucose levels and changes in the expression of enzymes involved in energetic metabolism were observed. However, serotonin levels did not significantly increase compared with the exposure to MDMA alone. Tramadol or tapentadol exposure did not cause a significant increase in serotonin levels compared with non-treated cells. Then, serotonergic toxicity may not be associated with the damage observed. Further studies are needed to better understand the toxicity deriving from the simultaneous exposure to these drugs. The results additionally underlined the need for a careful prescription of tramadol and tapentadol.